O uso de tecnologia por alunos do ensino fundamental: um estudo de caso - Marcia Moura de Onofre (2016)
This study investigated a group of elementary education students at a public school in the metropolitan area of Belo Horizonte, and tried to understand the extent of access they have to new digital technologies, and the use they make of these technologies. The objective was, thus, to understand the perceptions that these students have of the learning opportunities offered by these new technologies. In order to accomplish this, a case study was designed, in which an initial diagnosis of the group with regard to the access and use of new digital technologies was done. Subsequently, the participants produced comic stories both in the analog and digital formats. A final interview was conducted, in search of participants perceptions on these productions. The results showed limitations in participants use of new digital technologies with regard to the internet due to the weak internet signal, both in terms of mobile use on their smart phones and in the use of digital technologies in school. Results also showed that, through the production of these activities in two different formats, the analog and the digital, participants were able to perceive various types of literacies necessary for these productions. These results demonstrate the need for investment in the Internet network of public schools, which would provide an increased use of new technologies in schools, and therefore, the use of new literacies by students, thus providing an opening of horizons and allowing for the education of more capable and conscious citizens.